Pimozide treatment for delusion of infestation - Ungvári, G; Vladár, K (Activitas nervosa superior, 1986)
Pimozide was tried in the treatment of delusion of parasitosis (a type of monosymptomatic hypochondriacal psychosis), a syndrome that is found with increasing frequency. Ten patients were selected on the basis of unambiguously defined psychopathological criteria. Pimozide therapy was assessed by means of placebo control and the double-blind method using a rating scale evolved for this particular therapy. The results have quite definitely proved the effect of small doses (two to eight mg per day) of pimozide compared to the administration of a placebo. The very few side-effects observed could easily be influenced. The dynamics of the regression of the psychopathological symptoms suggest that the efficacy of pimozide therapy is decisively linked to the central dopamine receptor blocking effect of the drug.
Keywords: senioři; dvojitá slepá metoda; Double-Blind Method; Hypochondriasis; Time Factors; Middle Aged; mužské pohlaví; Pimozide; pimozid; hodnocení léčiv; Drug Evaluation; ženské pohlaví; Humans; časové faktory; hypochondrie; lidé středního věku; Parasitic Diseases; parazitární nemoci; Aged; Female; lidé; Male